The reasons for the violence of parents towards the teaching staff from the point of view of the directors of public schools in villages west of Ramallah - Abu Safiya, Ramadan Hassan; Abdel Razek, Khalil Ibrahim (Journal of Humanities & Social Sciences, 2022)
This study aims to identify the causes of parent’s violence towards the teaching staff from the point of view of the directors of governmental schools in villages west of Ramallah. The researchers used the descriptive analytical approach due to its suitability for the purposes of the study. They used the random sample method, distributed upon (24) retrieved, The study reached several results; the most important is that the causes of parent’s violence towards the teaching staff came in a high degree in the overall field, as the percentage of responses reached (71%). In addition, it was found that the highest areas represented in the family’s causes as its percentage reached (80%), and then the follower are the school’s reasons as their percentage reached (62%). Researchers attribute the rising phenomenon of parent’s violence towards the teaching staff to the absence of effective systems and laws that control the relationship between the two parties. In addition to the political conditions experienced by the Palestinian community, and the lack of awareness of the educational role that the teaching staff play during their dealing with students, which reinforces the phenomenon of violence by parents towards the teaching staff. The study recommends: Strengthening the level partnership relationship between faculty members and parents of students to reduce the problem of violence between the two parties by activating of the role of parent councils. And Enhance teachers’ active and constructive communication skills with students’ parents on a permanent and continuous basis.